Elimination of bacterial from in vitro yam tissue cultures using antibiotics - Mbah, E. I.; Wakil, S. M. (2012)
In vitro germplasm collections are always under the threat of air-borne microbial contaminants following poor laboratory practices and endogenous contaminants. Visibly clean cultures of aseptically micropropagated shoot cultures of plants of the genus Dioscorea (yam) grown on yam multiplication media are often contaminated with covert bacteria. The bacteria may survive endophytically within plantlets thereby making them unsuitable for in vitro maintenance of germplasm. The aim of this study was to evaluate and determine the efficacy of bactericidal doses of antibiotics on contaminated in vitro cultures of Dioscorea rotundata. Both single antibiotics [rifampicin (Rn) at 125 μg/ml], combination of two antibiotics [tetracycline plus rifampicin (TR), streptomycin plus gentamycin (SG) and vancomycin plus streptomycin (VS) each at 125 μg/ml] and combination of five antibiotics [tetracycline + vancomycin + streptomycin + gentamycin + rifampicin (TVSGR) at a final concentration of 100 μg/ml] were tested on contaminated cultures by growing non-disinfected nodal cuttings on a semi-solid yam multiplication media supplemented with the antibiotics for 3 to 4 weeks. During the period of antibiotic exposure, Rn, TR and TVSGR significantly (P>0.001) inhibited bacterial growth on non-disinfected cultures though without complete elimination. Further tests carried out with these three promising antibiotic treatments on both disinfected and non-disinfected in vitro yam cultures showed that only 33% of the yam genotype TDr 95/19177 treated with TVSGR were completely free from contaminating bacteria. Phytotoxicity (necrosis) was not observed between the first two weeks of antibiotic (Rn, TR and TVSGR) treatment but only after prolonged exposure.